Peran Ukuran Perusahaan dalam Memoderasi Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Publikasi Laporan Keuangan - Siti Noor Azizah; Adelina Citradewi (PUBLIKASI RISETMAHASISWA AKUNTANSI, 2026)
Timeliness of financial report publication is crucial to maintaining the relevance of information for decision making, particularly for investors and creditors. However, various factors, such as financial distress, profitability, and company age, can influence this timeliness. This issue arises because previous research on the influence of these three factors has shown inconsistencies. Thus, the purpose of this study is to examine how company size influences the timeliness of financial report publishing in relation to financial crisis, profitability, and company age. Secondary data for this quantitative research obtained from the annual financial reports of companies in the consumer cyclical sector and the property real estate sector listed on the Indonesia Stock Exchange (IDX) in 2024. 124 companies were chosen for the research sample using purposeful sampling. The data was analyzed using multiple linier regression and moderated regression analysis (MRA) in IBM SPSS Statistics 25. The use of firm size as a moderating variable that affects the link between the independent factors and reporting timeliness is what makes this study novel. The findings indicate that while profitability has no bearing on the timing of financial repot issuance, financial hardship and firm age do. Company size is only able to moderated the influence of profitability on the timeliness of financial report publication.